If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Simplifying y^{2}+ -16y + -4 = 0 Reorder the terms: -4 + -16y + y^{2}= 0 Solving -4 + -16y + y^{2}= 0 Solving for variable 'y'. Begin completing the square. Move the constant term to the right: Add '4' to each side of the equation. -4 + -16y + 4 + y^{2}= 0 + 4 Reorder the terms: -4 + 4 + -16y + y^{2}= 0 + 4 Combine like terms: -4 + 4 = 0 0 + -16y + y^{2}= 0 + 4 -16y + y^{2}= 0 + 4 Combine like terms: 0 + 4 = 4 -16y + y^{2}= 4 The y term is -16y. Take half its coefficient (-8). Square it (64) and add it to both sides. Add '64' to each side of the equation. -16y + 64 + y^{2}= 4 + 64 Reorder the terms: 64 + -16y + y^{2}= 4 + 64 Combine like terms: 4 + 64 = 68 64 + -16y + y^{2}= 68 Factor a perfect square on the left side: (y + -8)(y + -8) = 68 Calculate the square root of the right side: 8.246211251 Break this problem into two subproblems by setting (y + -8) equal to 8.246211251 and -8.246211251.## Subproblem 1

y + -8 = 8.246211251 Simplifying y + -8 = 8.246211251 Reorder the terms: -8 + y = 8.246211251 Solving -8 + y = 8.246211251 Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '8' to each side of the equation. -8 + 8 + y = 8.246211251 + 8 Combine like terms: -8 + 8 = 0 0 + y = 8.246211251 + 8 y = 8.246211251 + 8 Combine like terms: 8.246211251 + 8 = 16.246211251 y = 16.246211251 Simplifying y = 16.246211251## Subproblem 2

y + -8 = -8.246211251 Simplifying y + -8 = -8.246211251 Reorder the terms: -8 + y = -8.246211251 Solving -8 + y = -8.246211251 Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '8' to each side of the equation. -8 + 8 + y = -8.246211251 + 8 Combine like terms: -8 + 8 = 0 0 + y = -8.246211251 + 8 y = -8.246211251 + 8 Combine like terms: -8.246211251 + 8 = -0.246211251 y = -0.246211251 Simplifying y = -0.246211251## Solution

The solution to the problem is based on the solutions from the subproblems. y = {16.246211251, -0.246211251}

| y=5x^2-3x+5 | | 7x-28=2x^2-8x-3x+12 | | y=x^2+5x | | y=x^2+2x | | x^7-5x^5+x^2-5=0 | | 15x^2-8x-7=0 | | X^2+6x-27=0 | | 3x^2-6x+12=0 | | (4x^3-6x^2+5)-(8x^2+3x-6)= | | 11x^2-2x+9=0 | | 4x(2x^2-6x-5)= | | 10x^2+5x+8=0 | | 9x^2+9x+8=0 | | 12x^2+5x+10=0 | | 9x^2+21x+12=0 | | -2x^2+4x+12=0 | | 3x^2+10x+8=0 | | -8x^2+8x-2=0 | | X^2-x-2=0 | | 3x^2+x-1=0 | | (8x^4+5x^3-5)-(5x^2-6x+4)= | | 2x^2+10x+12=0 | | (7m^8-5m^3+9m^2+5)+(9m^7+3m^3-4m)= | | X^2-5x-48=0 | | X^2-12x+20=0 | | x^4-4x^3+5x^4-9x^3+2= | | (6x^4y^3+9x^3y^2)+(3x^3y^3-2x^3y^2-7xy)= | | y=x^3+3x^2-9x-8 | | 4x^4+3x^2-1=0 | | kx^2+4x+(5-k)=0 | | 12a^4b^3=0 | | 108x^4+360x^3+447x^2+245x+50=35 | | -35x^2-5x+30=0 | | 12x+2=3x^2 | | 2x^2+3x+5=0 | | (12x^2-3x-8)-(4x^2+5)= | | 5n+6n^4+3n-8n^4+n= | | 3n-2n^4+n+7n^4-2n= | | 12n-2n^4-10n-2n^4+n= | | X^2+16x+42=0 | | x^2+2x-288=0 | | 2x^2+3x-44=0 | | X^2+10x+22=6 | | x^5+x^4+x^3+x^2+x+3=0 | | x^2+6x-65=0 | | 56x+8x^2=0 | | x^2+6x+8=0 | | x^2+16x=-7 | | 3x^2-24x+1=0 | | 5x^2+6xy+13j^2= | | 2x^2+14x=120 | | 6r^2+11r-10=0 | | 6r^2+10r=0 | | y=4k^2+6k-1 | | 3x^2+16x+64=0 | | 2x^2+8x=90 | | 3x^2+12x=180 | | 4x^2+13x-75=0 | | 4x^2+13-75=0 | | 3x^2+10x-88=0 | | 2v^2-4v+52= | | v^2-4v+16= | | v^2-36= | | 24uxy^5-22u^5y^5= | | 4u^6+6u^5-10u^4= |

- Equations solver - equations involving one unknown
- Quadratic equations solver
- Percentage Calculator - Step by step
- Derivative calculator - step by step
- Graphs of functions
- Factorization
- Greatest Common Factor
- Least Common Multiple
- System of equations - step by step solver
- Fractions calculator - step by step
- Theory in mathematics
- Roman numerals conversion
- Tip calculator
- Numbers as decimals, fractions, percentages
- More or less than - questions